Journal Notes - various authors (GDR Bulletin, 1983)
Reviews of: Neue Deutsche Literatur, Vol. 30, No. 1-6 (Peter Beicken) Zeitschrift für Germanistik, No. 1 and 2, 1982 (Karl-Heinz Schoeps) Deutschland Archiv Vol. 15, No. 10-12 (Karen Remmler) Sinn und Form, Vol. 34, No. 3-4 (Wolfgang Ertl)